1983
DOI: 10.1182/blood.v62.2.286.bloodjournal622286
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-thalassemia is related to prolonged survival in sickle cell anemia

Abstract: We have determined the frequency of deletional alpha-thalassemia in black populations in the USA and Africa that harbor sickle cell anemia. In normals, the frequency of the chromosome bearing a deletion of one of the two normal alpha gene loci, designated (-alpha), ranged from 0.12 to 0.16, and in sickle trait subjects, the frequency ranged from 0.18 to 0.20. By contrast, in sickle cell anemia subjects, the frequency was significantly greater and ranged from 0.22 to 0.33. Analysis demonstrated that the greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Thus, patients with a thalassemia had less severe hemolytic anemia and lower leukocyte and platelet counts. To our knowledge, this impact on leukocytes and platelets has not been reported before and could possibly contribute to the beneficial effects of a thalassemia on patient survival 12 and frequency of crises 35 by lowering viscosity. At baseline, in the Baby-Hug trial, 36 patients with a thalassemia (75/189) had significantly lower MCV, mean corpuscular Hb, reticulocytes, and bilirubin levels, but leukocyte and platelet counts were not reported, and the presence of a thalassemia had no effect on Hb levels, probably in part because of the lower number of patients in their cohort, but the favorable impact of a thalassemia on Hb was only observed in CAR/ CAR patients and not in BEN/BEN patients in our study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Thus, patients with a thalassemia had less severe hemolytic anemia and lower leukocyte and platelet counts. To our knowledge, this impact on leukocytes and platelets has not been reported before and could possibly contribute to the beneficial effects of a thalassemia on patient survival 12 and frequency of crises 35 by lowering viscosity. At baseline, in the Baby-Hug trial, 36 patients with a thalassemia (75/189) had significantly lower MCV, mean corpuscular Hb, reticulocytes, and bilirubin levels, but leukocyte and platelet counts were not reported, and the presence of a thalassemia had no effect on Hb levels, probably in part because of the lower number of patients in their cohort, but the favorable impact of a thalassemia on Hb was only observed in CAR/ CAR patients and not in BEN/BEN patients in our study.…”
Section: Discussionmentioning
confidence: 63%
“…3 The presence of a thalassemia in SCA patients is known to reduce HbS polymerization and hemolysis by lowering intracellular Hb concentration [9][10][11] and improve anemia, and it has been reported to be associated with improved survival. 12 The HbS gene emerged and expanded through the selective pressure of Plasmodium falciparum malaria in separate geographic locations of Africa. 13 These distinct mutational events were identified by linked DNA polymorphic sites, located on the b-globin cluster, and defined as the Senegal (SEN), Benin (BEN), Bantu/Central African Republic (CAR), and Cameroon 14 haplotypes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] The oldest are now 43 years of age and the Cohort has allowed assessment of causes of death (COD) and survival to middle age in a hydroxyurea naïve population in which, for the past 30 years, interventions have included pneumococcal prophylaxis, training caregivers in splenic palpation and provision of comprehensive health care. The predictive effects of early life biomarkers of a severe clinical course (dactylitis before age 1 year or ever, a high total nucleated cell count or low hemoglobin at age one year),[ 4 ] as well as genetically determined phenotypes (alpha-thalassemia status,[ 5 ] beta-globin haplotype[ 6 ] and fetal haemoglobin[ 7 ] were assessed. Cause/s of death was assigned, where possible…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we did not evaluate our group for the presence of alpha thalassemia. Though some studies have suggested that patients with SCA and concomitant alpha thalassemia have decreased mortality rates, larger cohort studies have failed to bear out these findings [ 2 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%